Ocena wybranych aspektów jakości życia w grupie pacjentów z nadciśnieniem tętniczym = Evaluation of selected aspects of the quality of life in patients with hypertension - Sawicka, Katarzyna; Wieczorek, Alicja; Łuczyk, Robert; Wawryniuk, Agnieszka; Prasał, Marek (Journal of Education, Health and Sport, 2017)
Sawicka Katarzyna, Wieczorek Alicja, Łuczyk Robert, Wawryniuk Agnieszka, Prasał Marek. Ocena wybranych aspektów jakości życia w grupie pacjentów z nadciśnieniem tętniczym = Evaluation of selected aspects of the quality of life in patients with hypertension. Journal of Education, Health and Sport. 2016;6(11):161-178. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.164945 http://ojs.ukw.edu.pl/index.php/johs/article/view/3977 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 05.11.2016. Ocena wybranych aspektów jakości życia w grupie pacjentów z nadciśnieniem tętniczym Evaluation of selected aspects of the quality of life in patients with hypertension Katarzyna Sawicka1, Alicja Wieczorek1, Robert Łuczyk1, Agnieszka Wawryniuk1, Marek Prasał2 1 Katedra Interny z Zakładem Pielęgniarstwa Internistycznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 1Department of Internal Medicine with the Department of Internal Nursing, Faculty of Health Sciences, Medical University of Lublin 2 Katedra i Klinika Kardiologii, Uniwersytet Medyczny w Lublinie 2 Department of Cardiology, Medical University of Lublin Streszczenie Wstęp. W ostatnich latach coraz częściej w badaniach klinicznych, jak również w codziennej praktyce lekarskiej, dokonuje się oceny jakości życia chorych. Występowanie wzajemnych zależności pomiędzy funkcjonowaniem fizycznym, społecznym i emocjonalnym pacjentów a stopniem natężenia dolegliwości somatycznych sprawia, iż ocena jakości życia jest elementem bardzo ważnym w postępowaniu leczniczym. Wiedza na temat wpływu objawów a także poszczególnych sposobów leczenia ułatwia kompleksową ocenę skuteczności terapii, wybór strategii działania oraz określenie oczekiwań pacjentów. Na osiągnięcie rzetelnych i porównywalnych wyników dla oceny jakości życia pozwalają standaryzowane kwestionariusze jakości życia, które są wypełniane przez pacjenta. Specyficzne kwestionariusze przeznaczone są do pomiaru jakości życia osób z określonym schorzeniem. [1, 2]. Schorzenia układu sercowo-naczyniowego na skutek rozpowszechnienia, a także następstwa społeczne oraz ekonomiczne są szczególną dziedziną zainteresowań badaczy oceniających jakość życia. Bardzo ważne jest prawidłowe rozpoznanie a także leczenie nadciśnienia tętniczego. Choroba ta prowadzi do rozwoju wielu powikłań, głównie w układzie sercowo – naczyniowym. Najpoważniejszymi jej konsekwencjami są udar mózgu, zawał mięśnia sercowego, niewydolność nerek i choroby narządu wzroku. Szybkie wdrożenie odpowiedniego leczenia farmakologicznego oraz zmiana stylu życia i nawyków, przyczynia się do zmniejszenia rozwoju choroby a tym samym zapobiega wystąpieniu groźnych powikłań. Materiał i metoda. Badanie zostało przeprowadzone od grudnia 2015 roku do kwietnia 2016 roku. Grupę badaną stanowiły 103 osoby chorujące na nadciśnienie tętnicze. Osoby badane zostały poinformowane o anonimowości prowadzonego badania oraz o jego celu. Respondenci wyrażający chęć i zgodę wzięcia udziału w badaniu otrzymali kwestionariusz ankiety składający się z autorskiej metryczki oraz wystandaryzowanego narzędzia - kwestionariusza oceny jakości życia WHOQOL-BREF – wersja polska. Weryfikacji różnic między zmiennymi dokonano przy użyciu testów nieparametrycznych. Dwie grupy niezależne porównano za pomocą testu U Manna-Whitneya. Do porównania więcej niż dwóch grup niezależnych użyto testu H Kruskala-Wallisa. Przyjęto poziom istotności p < 0,05. Obliczeń dokonano za pomocą programu IBM SPSS Statistics 21. Wyniki. 1. Indywidualna ogólna percepcja jakości życia i własnego zdrowia jest lepsza wśród kobiet. Mężczyźni wskazują na lepszą jakość życia w domenie fizycznej i środowiskowej. 2. Respondenci do 60 roku życia wykazują znacznie lepszą jakość życia. Na jakość życia w każdej ze sfer: fizycznej, psychologicznej i relacji społecznych nie ma wpływu miejsce zamieszkania, wykształcenie czy status społeczny. 3. Z przeprowadzonych badań wynika, że czas trwania choroby wpływa na jakość życia badanych w domenie fizycznej. Im krótszy czas choroby, tym lepsza jakość życia. 4. Ilość stosowanych leków ma wpływ na jakość życia w domenie fizycznej. Najlepszą jakość życia mieli badani przyjmujący 1 lek. 5. U większości osób badanych rozpoznanie choroby ma duży wpływ na ich poczucie jakości życia. Słowa kluczowe: jakość życia, nadciśnienie tętnicze Abstract Admission. In recent years, more and more frequently in clinical trials, as well as in everyday medical practice, shall assess the quality of life of patients. The presence of interrelations between the functioning of physical, social and emotional patients and the degree of intensity of somatic complaints makes the evaluation of the quality of life is a very important element in medical treatment. Knowledge about the effects of the symptoms and various treatment methods facilitates comprehensive assessment of the efficacy of therapy, the choice of strategy, identifying the expectations of patients. To achieve reliable and comparable results for the evaluation of the quality of life allow standardized quality of life questionnaires that are completed by the patient. Specific questionnaires are designed to measure the quality of life of people with a specific disease. [1, 2]. Diseases of the cardiovascular system because of the prevalence, as well as social and economic consequences are a particular area of interest of researchers evaluating the quality of life. It is important that the correct diagnosis and treatment of hypertension. This disease leads to the development of many complications, mainly in the cardiovascular system - vasculature. The most serious are the consequences of stroke, myocardial infarction, renal failure and ocular diseases. Rapid implementation of appropriate pharmacological treatment and a change in lifestyle and habits, helps to reduce the progression of the disease and thus prevents the occurrence of serious complications. Material and methods. The survey was conducted from December 2015 to April 2016. The study group were 103 people suffering from hypertension. The subjects were informed about the anonymity of the survey and its purpose. Respondents expressing the desire and consent to participate in the study were given a questionnaire consisting of proprietary specifications and standardized tools - questionnaire assessing quality of life WHOQOL-BREF - Polish version. Verification of the differences between variables were performed using non-parametric tests. Two independent groups were compared by a test of Mann-Whitney. Compare with more than two groups of independent test was used Kruskal-Wallis H. The level of significance p<0.05. Calculations were performed using IBM SPSS Statistics 21. Results. 1. Individual general perception of quality of life and their health is better among women. Men show a better quality of life in the domain of physical and environmental. 2. The respondents to 60 years of age have a significantly better quality of life. The quality of life in each of the areas of physical, psychological, social relationships does not affect the place of residence, education, social status. 3. The study shows that the duration of the disease affects the quality of life of respondents in the physical domain. The sick shorter, the better the quality of life. 4. The amount of drugs affects the quality of life in the physical domain. The best quality of life were the subjects receiving 1 medicine. 5. The majority of the respondents diagnosis of the disease has a significant impact on quality of life. Keywords: quality of life, hypertension